THUKUL'S POEMS OF RESISTANCE IN AKU INGIN JADI PELURU - B. Retang Wohangara (Celt: A Journal of Culture, English Language Teaching & Literature, 2003)
Those who attempt to voice critically about the injustice done by the state frequently face the government's" iron hands ". Indonesia history has noted how some Indonesian critics from various fields are accused of threatening national stability so that they have to be culturized through many kinds of terror. Conscience writers (Mangunwijaya s term) are the easy targets of state violence because they portray the powerless, "wong cilik" (the common folk/little people) as the victims of development, and the inappropriateness of the elites' behavior. For an authoritative regime. such criticism doesn't sound good because it makes look bad in front of the public. In the New Order regime. Wiji Thukul is one of Indonesian poets who does an advocacy for "wong cilik ". His poems are screams of the people from huts,factories. and graves.